Antimicrobial susceptibility and integrons detection among extended-spectrum β-lactamase producing Enterobacteriaceae isolates in patients with urinary tract infection - Karzan Taha Abubaker; Khanda Abdulateef Anwar (PeerJ, 2023)
Background Integrons are bacterial mobile genetic components responsible for mediating the antibiotic resistance process by carrying and spreading antimicrobial resistance genes among bacteria through horizontal gene transfer. Objectives This cross-sectional hospital-based study aimed to find the prevalence of antibiotic resistance patterns and to detect integrons classes (I, II, and III) among bacterial isolates in patients with urinary tract infections (UTI) in Sulaimani, Iraq. Patients and Methods Mid-stream urine samples (no. = 400) were collected from patients with UTI at three different Hospitals from Sulaimani, Iraq, between September 2021 to January 2022. Urine samples were cultured on various agar media, and grown bacteria were isolated. Antibiotic susceptibility test (AST) and an extended-spectrum β-lactamase (ESBL) screen were done for isolated bacteria. Then, integrons classes were screened using conventional PCR with gene sequencing and uploaded to the National Center for Biotechnology Information (NCBI). Results The frequency rate of Enterobacteriaceae was 67.03% among positive urine cultures. E. coli (no. = 86) and Klebsiella pneumoniae (no. = 32) isolates were identified. The most sensitive antibiotics were the carbapenem group (85.3%) and nitrofurantoin (NFN) (64.2%), while the most resistant antibiotics were nalidixic acid (NA) and 3rd generation cephalosporin. The occurrence rate of ESBL was 56.6% with a predominance of class I integron (54.2%), then class II (15.8%) and no positive record for class III integron were observed. Conclusion Most bacterial isolates from patients with UTI produced class I and II integrons genes with favourable ESBL properties.